Theoretical studies of the CO2–N2O van der Waals complex : Ab initio potential energy surface, intermolecular vibrations, and rotational transition frequencies - Yang, Minghui (2013)
Theoretical studies of the potential energy surface and bound states were performed for the CO2–N2O van der Waals complex. A four-dimensional intermolecular potential energy surface (PES) was constructed from 11 466 ab initio data points which were calculated at the coupled-cluster single double (triple) level with aug-cc-pVTZ basis set supplemented with bond functions. Three co-planar local minima were found on this surface. They correspond to two equivalent isomers with a slipped parallel structure in which the O atom in N2O is near the C atom in CO2 and a T-shaped isomer in which the terminal N atom in N2O is closest to the C atom in CO2. The two slipped parallel isomers are energetically more stable than the T-shaped isomer by 178 cm−1. Four fundamental vibrational excited states for the slipped parallel isomers and two fundamental vibrational excited states (torsion and disrotation) for the T-shaped isomer were assigned via bound states calculations based on this PES. The theoretical vibrational frequencies are in good agreement with the available experimental values for the slipped parallel isomers. Rotational excitations (J = 0–6) for the ground vibrational state of the slipped parallel structure were calculated and the accuracy of the PES in the vicinity of minima is validated by the good agreement between the theoretical and experimental transition frequencies and spectroscopic parameters.